2018
DOI: 10.1371/journal.pone.0204483
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lauric acid on the susceptibility of chickens to an experimental Campylobacter jejuni colonisation

Abstract: Among the organic acids, lauric acid has shown a high level of in vitro activity against Campylobacter jejuni. The prevalence and intensity of C. jejuni excretion at slaughter often becomes lower with increasing age. In higher-aged broilers on organic farms which often use other breeds, in turn, the prevalence of C. jejuni is sometimes higher at slaughter. The question then arises as to whether a diet with higher lauric acid concentrations, the age alone or the genetic breed might have an effect in the spread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…jejuni in excreta samples of seeder birds (days 2, 11, and 17 after inoculation) and in caecal samples of all birds at dissection were performed during the experimental period in order to examine prevalence and excretion of C. jejuni . The results were already published in Hankel et al (2018). Three weeks after the experimental challenge with C .…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…jejuni in excreta samples of seeder birds (days 2, 11, and 17 after inoculation) and in caecal samples of all birds at dissection were performed during the experimental period in order to examine prevalence and excretion of C. jejuni . The results were already published in Hankel et al (2018). Three weeks after the experimental challenge with C .…”
Section: Methodsmentioning
confidence: 85%
“…jejuni took place in all subgroups. In accordance with Hankel et al (2018), three of 15 broilers of each subgroup (seeder birds) were administered orally with a 1 mL inoculum of C . jejuni (4.46 ± 0.35 log 10 CFU/mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter studies however concluded that, despite there was a reduction of protozoa, addition of up to 540 g/d of lauric acid was not enough to improve ruminal efficiency. Lauric acid has antimicrobial properties when fed to broilers or pigs [32,33]. The effect of lauric acid on rumen bacteria is less known.…”
Section: Effects Of Fatty Acids On Microbiota Of the Rumenmentioning
confidence: 99%